The Strategies Based Instruction to Improve Speaking Ability of UPB Class Students at STAI Darul Ulum Kandangan - Fahrinawati (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2022)
Meaningful and fluent communication is the ultimate goal of English as foreign language (EFL) learners in teaching and learning English, but the language learners faced communication problems when they attempt to use the target language. Introducing and teaching the learners with learning strategies, specifically communication strategy is a plausible solution to the learners’ communication problem. The teaching of communication strategies commonly known as strategies based instruction. This study investigated the implementation of strategies based instruction to improve students speaking ability of UPB Class at STAI Darul Ulum Kandangan. The strategies based instruction was implemented in explicitly and implicitly way and it embedded into the teaching and learning material. The result showed that the strategies based instruction which was implemented in the classroom to embed the learners’ awareness to use the communication strategies facilitated the learners to be more responsible in using the target language. It could be seen from students’ use of some communication strategies to solve their speaking problems in oral performance. This strategy also helped the learners to reduce the use of mother tongue and make their speaking more comprehensive.